Doping in Martial Arts: How Is It Managed? - Agung Nugroho; Arko Jatmiko Wicaksono; Hary Widodo; Santosa Budiharjo; Djoko Pekik Irianto; Rustamaji Rustamaji; Lismadiana Lismadiana (Journal of Coaching and Sports Science)
Background: Doping remains a persistent issue in martial arts, exacerbated by the easy access to over-the-counter medications containing banned substances. Despite existing regulations, athletes often lack comprehensive knowledge of anti-doping measures, leading to unintentional violations.